2020
DOI: 10.1038/s41467-020-19960-x
|View full text |Cite
|
Sign up to set email alerts
|

A FN-MdV pathway and its role in cerebellar multimodular control of sensorimotor behavior

Abstract: The cerebellum is crucial for various associative sensorimotor behaviors. Delay eyeblink conditioning (DEC) depends on the simplex lobule-interposed nucleus (IN) pathway, yet it is unclear how other cerebellar modules cooperate during this task. Here, we demonstrate the contribution of the vermis-fastigial nucleus (FN) pathway in controlling DEC. We found that task-related modulations in vermal Purkinje cells and FN neurons predict conditioned responses (CRs). Coactivation of the FN and the IN allows for the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 85 publications
5
26
0
Order By: Relevance
“…The data on suppression PCs in the medial cerebellum showing a relatively early SS modulation during execution of both pro- and antisaccades as well as those on facilitation PCs in the lateral cerebellum showing a prominent modulation at the end of the instruction of antisaccades indicate that different modules of different cerebellar regions can simultaneously contribute to the same complex behavior, yet with different particularities. A similar conclusion was drawn from a recent study on delay eyeblink conditioning (Wang et al, 2020). Even though this form of conditioning is classically considered to be controlled solely by modules in lobule simplex of the lateral cerebellum, Wang and colleagues have shown that modules of the medial cerebellum are equally essential, yet also contributing in a slightly differential fashion, possibly regulating mainly muscle tone.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The data on suppression PCs in the medial cerebellum showing a relatively early SS modulation during execution of both pro- and antisaccades as well as those on facilitation PCs in the lateral cerebellum showing a prominent modulation at the end of the instruction of antisaccades indicate that different modules of different cerebellar regions can simultaneously contribute to the same complex behavior, yet with different particularities. A similar conclusion was drawn from a recent study on delay eyeblink conditioning (Wang et al, 2020). Even though this form of conditioning is classically considered to be controlled solely by modules in lobule simplex of the lateral cerebellum, Wang and colleagues have shown that modules of the medial cerebellum are equally essential, yet also contributing in a slightly differential fashion, possibly regulating mainly muscle tone.…”
Section: Discussionsupporting
confidence: 88%
“…A similar conclusion was drawn from a recent study on delay eyeblink conditioning 70 . Even though this form of conditioning is classically considered to be controlled solely by modules in lobule simplex of the lateral cerebellum 35 , Wang and colleagues have shown that modules of the medial cerebellum are equally essential, yet also contributing in a slightly differential fashion, possibly regulating mainly muscle tone 70 . Interestingly, similar to the current pro- and antisaccade tasks, during eyeblink conditioning the medial and lateral cerebellum also both engage facilitation and suppression cells, and they also operate at relatively low and high baseline firing frequencies, respectively 38,70 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Three nuclei in the DCN, except for the posterior IPN, appear to contribute substantially to regulation of the pontomedullary reticular formation, which is the main source of the reticulospinal tract controlling posture and locomotion ( Prentice and Drew, 2001 ; Stapley and Drew, 2009 ). In addition, a recent study demonstrated that the pathway from the cerebellar vermis to the contralateral ventral medullary reticular formation through the FN contributes to the delay eyeblink conditioning by cooperating with the canonical pathway of simplex lobule-anterior IPN-RN ( Wang et al, 2020 ).…”
Section: Historically Studied Efferent Pathways Of the Cerebellummentioning
confidence: 99%
“…The major researches of the last decades have provided the key proves of role of lobulus simplex of cerebelli and interposed nucleus in eyeblink conditioning and fine motor skills retardation [15]. These areas receive inputs from both mossy and climbing fibers, which transmit the signals of conditioned and unconditioned stimuli.…”
Section: Onementioning
confidence: 99%